Pemanfaatan Bottom Ash PLTU sebagai Media Filter untuk Mengolah Limbah Tahu - Yunita, Irda; Teuku Muhammad Zulfikar; Fiki Angga Mulia; Elvitriana; Bahagia (Jurnal Serambi Engineering, 2026)
Liquid waste from the tofu industry is a significant source of water pollution, containing high levels of organic materials that can harm aquatic ecosystems. On the other hand, Coal-Fired Power Plants (CFPP) produce a large amount of bottom ash, which is still underutilized. This study aims to explore the potential of bottom ash from the Nagan Raya CFPP in Aceh as an economical and environmentally friendly alternative filter medium for treating tofu wastewater. The main focus is to evaluate the effectiveness of bottom ash in reducing Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), and neutralizing pH. The method employed is a quantitative experimental approach using a layered filtration system consisting of gravel, coir, sand, and bottom ash as the adsorbent. The contact time between the wastewater and the filter medium was varied for 2, 4, and 6 hours, with a control filter without bottom ash. Initial samples showed TSS levels of 560 mg/L and a pH of 3.8, which are far below the quality standards. The results indicate that the use of bottom ash significantly improves wastewater quality, with the highest TSS removal efficiency reaching 82.85% at a contact time of 6 hours, reducing TSS to 96 mg/L. The highest COD reduction occurred at a contact time of 2 hours, with an efficiency of 24.8%. Bottom ash was also effective in neutralizing the wastewater, raising the pH to a neutral range (6.2 – 7.0). These findings suggest that bottom ash from CFPP has great potential as a filter medium for tofu wastewater.